HUBUNGAN SPIRITUALITAS DENGAN KUALITAS HIDUP LANSIA RW 001 SUDIMARA JAYA CILEDUG KOTA TANGERANG - Mutiara Zahira Fajri (2021)
Increasing age will cause a decrease in health status followed by the presence of various diseases, body balance, decreased body functions, and the risk of falling. The elderly are in a phase where they face physical, social, and mental health problems that will have an impact on their quality of life. The purpose of this study was to determine the relationship between spirituality and the quality of life of the elderly RW 001 Sudimara Jaya Ciledug, Tangerang City. The type of research used by the researcher is the quantitative correlation with a cross-sectional design which aims to connect the variables in this study. A simple random sampling technique was used in the study to take samples with 114 elderly respondents from RW 001 Sudimara Jaya Ciledug, Tangerang City with criteria aged 45 years and not having hearing or vision impairment. Data collection was done by using a questionnaire. The questionnaire instruments used were the demographic data questionnaire, the Daily Spiritual Experience Scale (DSES) questionnaire to measure spirituality, and the WHOQOL-BREF questionnaire to measure the quality of life. The results of statistical tests using chi-square showed a p-value of 0.017 (p-value <0.05), it can be concluded that there is a relationship between spirituality and quality of life in the elderly at RW 001 Sudimara Jaya Ciledug, Tangerang City. Good spirituality for the elderly themselves, their families, and also nurses as nursing care providers can help the elderly in improving their quality of life.